El papel del marcador como en la contextualización de metáforas y escenarios en la producción discursiva - Ciapuscio, Guiomar (2025)
This paper aims at contributing  to the investigation of markers in Spanish, specifically   the marker como, and in its combinations with que and cuando, from the approach of discursive production (Ciapuscio, 2003, 2022; Gülich and Kotschi, 1995; Gülich, 2006). The aim is to determine and characterize the functions of this marker in the context of formulating activities, especially, when it is used in metaphorical illustrations and scenario procedures, which are intended to facilitate the transmission of events and concepts that are difficult to describe (Brünner and Gülich, 2002; Ehmer, 2013). We conducted a qualitative analysis on a corpus of natural conversations between adults, on the one hand, and adolescents on the other, collected in the Buenos Aires region of Argentina, where the salient feature is the asymmetry of knowledge between interlocutors. We confirm the polyfunctional character of the marker that acts as an attenuator at the interactional level and, simultaneously, serves as  an indicator of metaphors and analogies (alone or followed by que), and of scenarios (followed by cuando). The results provide evidence for the thesis that the formulation constitutes a differentiated dimension, which acts as a kind of interface between the different textual components.